The biology of chronic myeloid leukemia: an overview of the new insights and biomarkers - Sicuranza, Anna; Cavalleri, Alessia; Bernardi, Simona (Frontiers in Oncology, 2025)
Chronic myeloid leukemia is one of the onco-hematologic diseases in which the identification of disease markers and therapeutic advances have been particularly impactful. Despite this, significant gaps remain in our understanding of disease pathogenesis, progression, mechanisms of immune escape, and resistance to standard therapies. Recently, advances in technology and biological knowledge have drawn attention to several promising areas of research. Among these, leukemic stem cells, miRNAs, extracellular vesicles, and additional BCR::ABL1 mutations, with particular reference to the ASXL1 gene, have been the most extensively investigated. In this review we summarized and critically commented the main findings on these key topics over the past 5 years, evaluating their potential impact on patient management and their role in the development of new therapeutic strategies.